Tackling the challenge of treating obesity using design research methods: A scoping review. (20th September 2021) - Elliott, Andrea; Lang, Sarah; Truby, Helen; Brennan, Linda; Gibson, Simone
Summary: Design research methods, including user‐centered design, human‐centered design, and design thinking, are iterative processes and frameworks that engage stakeholders to inform the design of initiatives, programs, or research interventions. Design research methods are not yet widely applied in healthcare. To date, there is a limited understanding of how design research methodologies can be applied to develop client‐centered weight loss interventions. This scoping review explores the extent, range, and nature of research projects that used design research methods to guide the development of an obesity treatment intervention. A systematic search of eight databases identified projects that used design research methods to develop a weight loss intervention or strategy. The method and practical application of design research processes for each eligible article were extracted and explored. Design research methods were used to generate ideas or guide the development of a mobile application ( n  = 6), mHealth device ( n  = 1), eHealth solution ( n  = 1), health promotion program ( n  = 1), or patient–clinician communication tools ( n  = 2). There was considerable variation in the application of design research processes between studies. Design research methods may provide an iterative, flexible framework to facilitate the development of client‐centered, inclusive interventions and strategies. Design research methods may support research teams to move away from the one‐size‐fits‐all approach to obesity treatment.